The The perceived value in ecotourism related to satisfaction and loyalty: a study from Costa Rica - Carvache-Franco, Mauricio; Perez-Orozco, Allan; Carvache-Franco, Orly; Víquez-Paniagua, Ana Gabriela; Carvache-Franco, Wilmer (Geographica Pannonica, 2020)
Ecotourism allows activities in contact with nature in protected natural areas to contribute to environmental care. This study seeks to establish the dimensions of perceived value in ecotourism and analyze its relationship with satisfaction and loyalty. It was an in situ research carried out in two protected areas of Costa Rica: Arenal National Park and Caño Negro National Wildlife Refuge. The sample consisted of 310 surveys for domestic and foreign tourists. The data were interpreted through a factorial analysis to identify the dimensions that make up the perceived value. Also, Spearman’s correlation technique and the stepwise multiple regression method were used to find the relationships among the variables. The findings show that there are three dimensions of perceived value: economic-functional, emotional, and social. Overall satisfaction and loyalty had a high average score, and the dimensions found are significantly and positively related to overall satisfaction. The “economic-functional value” dimension has a greater influence on overall satisfaction, and the “emotional value” dimension is the most significant predictor of the intentions to return, recommend, and say positive things about the ecotourism destination.